2016
DOI: 10.3892/ol.2016.4406
|View full text |Cite
|
Sign up to set email alerts
|

Expression of endothelin-1 in laryngocarcinoma tissues and its clinical significance

Abstract: In recent years, the incidence of laryngeal carcinoma has been on the increase. The aim of the present study was to examine the expression level of endothelin-1 (ET-1) in laryngeal carcinoma tissues and to establish its clinical significance. A total of 82 cases of laryngeal carcinoma tissues were examined, of which 27 cases were stage I, 34 were stage II, and 21 were stage III. The normal mucosal tissues beyond the surgical incision margin in the 82 laryngeal carcinoma patients were used as the normal control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
2
1
0
Order By: Relevance
“…The present study showed a significant association of ET-1 expression with the advanced stage of CSCC cases and positive lymph node metastasis. Similarly, high ET-1 expression and higher stages of laryngeal carcinoma were found to be associated in other studies (7,19). This could be explained by the fact that the ET-1/ETAR axis can promote EMT, thus enhancing invasion and metastasis.…”
Section: Discussionsupporting
confidence: 63%
“…The present study showed a significant association of ET-1 expression with the advanced stage of CSCC cases and positive lymph node metastasis. Similarly, high ET-1 expression and higher stages of laryngeal carcinoma were found to be associated in other studies (7,19). This could be explained by the fact that the ET-1/ETAR axis can promote EMT, thus enhancing invasion and metastasis.…”
Section: Discussionsupporting
confidence: 63%
“…In the current study, most of our studied meningioma cases (84%) showed positive MUC4 immunohistochemical expression and this was in concordance with Kong et al, 2020, Matsuyama et al, 2018 and Hasaneen et al, 2020 as 100%, 92.9% and 83.3% of their enrolled meningioma cases showed MUC4 positive immunohistochemical expression respectively [18][19][20] . Kong et al, 2020 reported that highest positivity was reported in meningothelial and secretory meningioma (100%), followed by 97.8% in angioma-tous meningiomas, 90.2% in atypical meningiomas and lowest in fibroblastic meningioma (13.5%) [18] . Similar figures were reported in our study as 100%; 12/12 of meningothelial and 7/7 of atypical meningiomas were positive for MUC4 followed by angiomatous meningioma (75%, 3/3) while only (1/6, 16.7%) of fibroblastic meningiomas were MUC4 positive.…”
Section: Discussionsupporting
confidence: 91%
“…The pathological type of laryngeal cancer is mainly squamous cell carcinoma. Studies have shown that the morbidity of laryngeal cancer is increasing (2,3). In the United States, the increase of new patients with laryngeal cancer total 12,000 cases each year.…”
Section: Introductionmentioning
confidence: 99%